A comparison of displacement and energetic variables between three team sport GPS devices. (3rd September 2018) - Terziotti, Paolo; Sim, Marc; Polglaze, Ted
ABSTRACT: This study compared the outputs of three different commercially-available GPS player-tracking devices for a range of commonly used displacement and energetic variables in activities replicating team sport movements. Professional male soccer players ( n = 7), simultaneously wore three GPS devices (Catapult OptimEye S5, GPExe Pro 1, StatSport ViperPod) whilst completing four separate drills, comprising progressively more complex changes in speed and direction. Displacement (distance, speed) and energetic (energy cost, metabolic power, energy expenditure) variables were compared for each device. All three devices tended to under-estimate distance compared to the known value for each drill, with only minor and inconsistent differences between devices. There were no differences between devices for average speed. For energetic variables, substantial differences were found between each device, and these differences magnified as movement tasks became more erratic. Given that energetic variables are derived from measures of instantaneous speed, and also incorporate the magnitude and direction of change between successive data points, these differences may be attributable to disparities in raw data quality, filtering techniques and calculation methods. In order to provide comparable estimates of energetic variables in team sports, player-tracking devices must be capable of accurately recording instantaneous velocity in activities comprising frequent changes in speed and direction.